PENERAPAN SKEMA WETTING AND DRYING PADA PERSAMAAN HIDRODINAMIKA UNTUK SIMULASI RAYAPAN GELOMBANG - Fitri Riandini (JURNAL SUMBER DAYA AIR, 2009)
Wetting and drying (WAD) are common and important phenomena of the coastal ocean. They occur inlow-lying coastal zones and also in embayment and inlets. Strong winds and/or tides can cause flooding andsubsequent drying. In shallow water models, wetting and drying are determined by the total depth D = 0 for'dry' and D>0 for 'wet'. The scheme defines 'dry' cells as region with a thin film fluid. The primitiveequations are solved in the thin film as well as in other regular wet cells. The scheme was applied tohydrodynamics model to simulate tsunami's run up at Banda Aceh (Nanggroe Aceh Darussalam) andPangandaran (West Java). Simulation results show that run up height at Banda Aceh reach more than 5 m,while at Pangandaran more than 3 m.